AMS Dating of the Late Copper Age Varna Cemetery, Bulgaria. Issue 2 (1st March 2018) - Higham, Thomas; Slavchev, Vladimir; Gaydarska, Bisserka; Chapman, John
Abstract: The Varna I cemetery, on the Bulgarian Black Sea coast, is one of the most remarkable sites in European prehistory, with the world's earliest large-scale assemblage of gold artifacts. Modeling of the first series of 14 accelerator mass spectrometry (AMS) dates yielded a duration of occupation at the site of ca. 150 years, 4600–4450 cal BC. However, there were insufficient paired human–animal dates for a full consideration of the question of the marine reservoir effect. Here, a fuller set of 71 dates from 53 graves is presented. We identify a small reservoir effect in a number of individuals based on 14 C, as well as carbon and nitrogen stable isotopes. We test the effect of this by building a series of different Bayesian models. Our favored model, including a correction for some of the human determinations, shows activity at the cemetery starting at 4596–4516 cal BC and ending 4427–4341 cal BC (at 95.4% probability). The overall span of activity covers 120–260 years (93.6% prob.). The modeling shows that Varna I falls toward the beginning of the Bulgarian Late Copper Age.